130k views
1 vote
Solve for x
x − 13 = 6x

x =

1 Answer

2 votes

Answer:

The correct answer is x = -13/5.

Explanation:

To solve this problem, we need to bring all of the x terms to one side of the equation and all of the constant terms to the other side of the equation.

First, we should subtract x from both sides to cancel out the positive x on the left side of the equation. This is modeled below:

x - 13 = 6x

x - x - 13 = 6x - x

- 13 = 5x

Next, we should divide both sides by 5 in order to get the variable x completely isolated on the right side of the equation.

-13/5 = 5x/5

-13/5 = x

Therefore, your answer is x = -13/5.

Hope this helps!

User Jonathan Watmough
by
5.6k points